2018
DOI: 10.1159/000486675
|View full text |Cite
|
Sign up to set email alerts
|

Serous Carcinoma of the Uterine Cervix, an Extremely Rare Aggressive Entity: A Literature Review

Abstract: Background/Aims: Serous carcinoma of the uterine cervix (USCC) is an extremely rare subtype. To establish the treatment strategy in patients with USCC is an important issue. Methods: MEDLINE (PubMed) was searched for all articles published after the first publication by Lurie et al. [Eur J Obstet Gynecol Reprod Biol 1991; 40: 79–81], reporting woman diagnosed with USCC. Because of limited numbers of studies on the topic of the study, we could not keep a restriction of eliminating smaller sample sizes. Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…Other studies have reported high-risk HPV DNA in 0%–75% of cases. [ 6 17 18 19 ] In the present study, two (29%) cases were of positive HPV DNA (type 18), which supports a weak association with SACC development. Further studies are needed to investigate the association between HPV infection and the occurrence of SACC.…”
Section: Discussionsupporting
confidence: 64%
See 4 more Smart Citations
“…Other studies have reported high-risk HPV DNA in 0%–75% of cases. [ 6 17 18 19 ] In the present study, two (29%) cases were of positive HPV DNA (type 18), which supports a weak association with SACC development. Further studies are needed to investigate the association between HPV infection and the occurrence of SACC.…”
Section: Discussionsupporting
confidence: 64%
“…described the molecular features of SACC, and concluded that it is usually positive for p16, carcinoembryonic antigen (CEA), CA-125, or p53 and negative for WT-1, estrogen, progesterone, PAS, or vimentin. In previous reports, percentage p53 immunopositivity ranged from 42% to 90%[ 5 6 13 ] and p53 expression was associated with poorer clinical outcomes. [ 5 8 11 14 ] These reports indicate that strong p53 expression is associated with recurrence, metastases, and death, and that assessment of p53 status might be prognostically meaningful.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations